Sylvatic rabies and the perception of vampire bat activity in communities in the Ecuadorian Amazon - Natalia Romero-Sandoval; Natalia Escobar; Mireia Utzet; Maria Feijoo-Cid; Miguel Martin (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
An outbreak of sylvatic rabies was reported in indigenous communities located in the Ecuadorian Amazon in November 2011. The objective of this study was to analyze family dwelling characteristics and other sociodemographic factors associated with the perception of an increase in hematophagous bat bites in humans and domestic animals to assist the implementation of intervention policies in the region. A total of 381 households from communities covered by the outbreak response activities were surveyed. Despite being associated with poorer dwelling conditions, the possession of domestic animals is associated with the perception of an increase in bat bites among animals. Better dwelling conditions, use of protective measures, access to electricity, and no domestic animals are variables associated with the perception of a rise in attacks on humans. The analysis of perceptions of bite frequency is fundamental to improve the effectiveness of vaccination programs and strategies to promote the adoption of preventive measures against rabies among the population.